Nd and Mn co-doped sodium bismuth titanate based ferroelectric film and preparation method and application thereof
By introducing Nd and Mn elements into the sodium bismuth titanate-based ferroelectric film, a co-doped ferroelectric film is formed, which solves the problem of low energy density of the dielectric capacitor and achieves a significant increase in energy storage density.
Patent Information
- Application Number
- CN202411804936.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-14
AI Technical Summary
The energy density of existing dielectric capacitors is low, resulting in large volume and heavy weight, making it difficult to meet the development needs of lightweight and miniaturization.
Using a sodium bismuth titanate-based ferroelectric film co-doped Nd and Mn, the Nd and Mn elements were introduced into the perovskite ABO3 structure respectively to form (Na0.3Bi0.7-xNdx) (Mg0.2Zr0.2Ti0.6 -yMny)O3 ferroelectric film.
The breakdown electric field strength was significantly improved, the maximum polarization reached 95μC/cm2, and the energy storage density increased from 67.99J/cm3 to 111.34J/cm3, an increase of about 65%.
Smart Images

Figure CN119430916A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ferroelectric thin-film capacitor technology, and in particular to a sodium bismuth titanate-based ferroelectric thin film co-doped with Nd and Mn, its preparation method, and its application. Background Technology
[0002] Dielectric capacitors, due to their unique energy storage mechanism, are attracting increasing attention in today's rapidly developing electronics industry. Their ultra-fast charge and discharge rates and ultra-high discharge power enable their widespread application in areas such as green energy storage, pulsed power systems, grid-connected systems, and new energy vehicle power systems. However, current dielectric capacitors have relatively low energy density, necessitating larger volumes for their use in energy systems. This contradicts the development theme of lightweight and miniaturization, making the research and development of new dielectric capacitors with high energy density, small size, and light weight particularly important. From the principle of electrostatic storage, we know that the energy density of dielectric materials is mainly determined by their breakdown strength and polarization strength. Therefore, how to simultaneously improve both of these strengths is a challenge currently facing researchers. Summary of the Invention
[0003] The purpose of this invention is to provide a sodium bismuth titanate-based ferroelectric thin film co-doped with Nd and Mn, its preparation method and application, to solve the technical problems of low energy density and large size of capacitors in the prior art.
[0004] To achieve the above-mentioned objectives, the present invention provides the following technical solution:
[0005] This invention provides an Nd and Mn co-doped sodium bismuth titanate-based ferroelectric thin film, wherein the chemical composition of the Nd and Mn co-doped sodium bismuth titanate-based ferroelectric thin film is: (Na 0.3 Bi 0.7-x Nd x (Mg) 0.2 Zr 0.2 Ti 0.6-y Mn y )O3, where 0≤x≤0.07, 0≤y≤0.04.
[0006] This invention also provides a method for preparing Nd and Mn co-doped sodium bismuth titanate-based ferroelectric thin films, comprising the following steps:
[0007] 1) Sodium acetate, bismuth nitrate, neodymium nitrate, and magnesium acetate were added to acetic acid in sequence according to the stoichiometric ratio to obtain solution A;
[0008] 2) According to the stoichiometric ratio, manganese nitrate, acetylacetone, tetrabutyl titanate, deionized water, zirconium propoxide and ethylene glycol are added sequentially to acetic acid to obtain solution B;
[0009] 3) Mix solution A and solution B and then age them to obtain the precursor solution;
[0010] 4) Spin-coat the precursor solution onto the substrate, then dry and heat-treat the substrate;
[0011] 5) Repeat step 4) until the target thickness is reached, then anneal to obtain (Na) 0.3 Bi 0.7-x Nd x (Mg) 0.2 Zr 0.2 Ti 0.6-y Mn y O3 ferroelectric thin film, where 0≤x≤0.07, 0≤y≤0.04.
[0012] Furthermore, the volume ratio of acetylacetone, deionized water and ethylene glycol is 1-3:2-4:3-8;
[0013] In step 1), the ratio of acetic acid to sodium acetate is 12-20 mL: 0.003 mol.
[0014] In step 2), the ratio of acetic acid to zirconium n-propoxide is 12-20 mL: 0.002 mol.
[0015] Furthermore, the total concentration of metal cations in the precursor solution is 0.2–0.4 mol / L; and the aging time is 1–7 days.
[0016] Furthermore, the spin coating speed is 2500–4500 r / min, the spin coating time is 30–40 s, and the substrate is a Si / Pt wafer.
[0017] Furthermore, the drying temperature is 200–250°C, and the drying time is 3–5 minutes.
[0018] Furthermore, the heat treatment is divided into two stages: the first stage is pyrolysis at 400-500℃ for 4-12 minutes, and the second stage is holding at 700-800℃ for 4-10 minutes.
[0019] Furthermore, the annealing temperature is 700–800°C, and the annealing time is 8–20 minutes.
[0020] Furthermore, the (Na) 0.3 Bi 0.7-x Nd x (Mg) 0.2 Zr 0.2 Ti 0.6-y Mn yThe thickness of the O3 ferroelectric thin film is 300-500 nm.
[0021] The present invention also provides an application of Nd and Mn co-doped sodium bismuth titanate-based ferroelectric thin film in the preparation of capacitors, wherein the structure of the capacitor from bottom to top is: a Si, Pt, Nd, Mn co-doped sodium bismuth titanate-based ferroelectric thin film and Au.
[0022] The beneficial effects of this invention are:
[0023] This invention obtains (Na) by introducing Nd and Mn elements into the A-site and B-site of the perovskite ABO3 structure, respectively. 0.3 Bi 0.7-x Nd x (Mg) 0.2 Zr 0.2 Ti 0.6-y Mn y O3 ferroelectric thin film. Compared with the original composition, the breakdown electric field strength is increased by 80%, and the maximum polarization reaches 95 μC / cm. 2 The energy storage density is 67.99 J / cm³. 3 Increased to 111.34 J / cm 3 This represents an increase of approximately 65%. Attached Figure Description
[0024] Figure 1 (Na) prepared in this invention 0.3 Bi 0.7-x Nd x (Mg) 0.2 Zr 0.2 Ti 0.6-y Mn y )Schematic diagram of the structure of O3 ferroelectric thin film microcapacitor;
[0025] Figure 2 The frequency-dielectric property curves of the ferroelectric thin film materials prepared in Examples 1-3 and Comparative Example 1 are shown.
[0026] Figure 3 The leakage current density curves of the ferroelectric thin film materials prepared in Examples 1-3 and Comparative Example 1 are shown.
[0027] Figure 4 Hysteresis loop diagrams of the ferroelectric thin film materials prepared in Examples 1-3 and Comparative Example 1;
[0028] Figure 5 The diagram shows a comparison of the breakdown strength and polarization intensity of the ferroelectric thin film materials prepared in Examples 1-3 and Comparative Example 1.
[0029] Figure 6 This is a comparison chart of the energy storage density and efficiency of the ferroelectric thin film materials prepared in Examples 1-3 and Comparative Example 1. Detailed Implementation
[0030] This invention provides an Nd and Mn co-doped sodium bismuth titanate-based ferroelectric thin film, wherein the chemical composition of the Nd and Mn co-doped sodium bismuth titanate-based ferroelectric thin film is: (Na 0.3 Bi 0.7-x Nd x (Mg) 0.2 Zr 0.2 Ti 0.6-y Mn y )O3, where 0≤x≤0.07, 0≤y≤0.04.
[0031] In this invention, x is preferably 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, or 0.07, and y is preferably 0, 0.01, 0.02, 0.03, or 0.04.
[0032] The Nd and Mn co-doped sodium titanate-based ferroelectric thin film is preferably (Na... 0.3 Bi 0.69 Nd 0.01 (Mg) 0.2 Zr 0.2 Ti 0.59 Mn 0.01 O3, (Na) 0.3 Bi 0.68 Nd 0.02 (Mg) 0.2 Zr 0.2 Ti 0.585 Mn 0.015 O3, (Na) 0.3 Bi 0.67 Nd 0.03 (Mg) 0.2 Zr 0.2 Ti 0.58 Mn 0.02 )O3.
[0033] This invention also provides a method for preparing Nd and Mn co-doped sodium bismuth titanate-based ferroelectric thin films, comprising the following steps:
[0034] 1) Sodium acetate, bismuth nitrate, neodymium nitrate, and magnesium acetate were added to acetic acid in stoichiometric proportions to obtain solution A;
[0035] 2) According to the stoichiometric ratio, manganese nitrate, acetylacetone, tetrabutyl titanate, deionized water, zirconium propoxide and ethylene glycol were added to acetic acid in sequence to obtain solution B;
[0036] 3) Mix solution A and solution B and then age them to obtain the precursor solution;
[0037] 4) Spin-coat the precursor solution onto the substrate, then dry and heat-treat the substrate;
[0038] 5) Repeat step 4) until the target thickness is reached, then anneal to obtain (Na) 0.3 Bi 0.7-x Nd x (Mg) 0.2 Zr 0.2 Ti 0.6-y Mn y O3 ferroelectric thin film, where 0≤x≤0.07, 0≤y≤0.04.
[0039] In this invention, the volume ratio of acetylacetone, deionized water and ethylene glycol is 1-3:2-4:3-8, preferably 1.2-2.8:2.2-3.8:4-7, and more preferably 1.5-2.5:2.5-3.5:5-6;
[0040] In step 1), the ratio of acetic acid to sodium acetate is 12-20 mL: 0.003 mol, preferably 15-18 mL: 0.003 mol, and more preferably 16-17 mL: 0.003 mol.
[0041] In step 2), the ratio of acetic acid to zirconium propoxide is 12-20 mL: 0.002 mol, preferably 15-18 mL: 0.002 mol, and more preferably 16-17 mL: 0.002 mol.
[0042] In this invention, the total concentration of metal cations in the precursor solution is 0.2–0.4 mol / L, preferably 0.3 mol / L; the aging time is 1–7 days, preferably 2–6 days, and more preferably 3–5 days.
[0043] In this invention, the spin coating speed is 2500-4500 r / min, preferably 2800-4000 r / min, and more preferably 3000-3500 r / min; the spin coating time is 30-40 s, preferably 32-38 s, and more preferably 35 s; the substrate is preferably a Si / Pt wafer.
[0044] In this invention, the drying temperature is 200-250°C, preferably 210-240°C, and more preferably 220-230°C; the drying time is 3-5 minutes, preferably 4 minutes.
[0045] In this invention, the heat treatment is divided into two stages: the first stage is pyrolysis at 400-500℃ for 4-12 min, and the second stage is holding at 700-800℃ for 4-10 min; preferably, the first stage is pyrolysis at 420-480℃ for 5-10 min, and the second stage is holding at 720-780℃ for 5-9 min; more preferably, the first stage is pyrolysis at 440-460℃ for 6-8 min, and the second stage is holding at 740-760℃ for 6-8 min.
[0046] In this invention, the annealing temperature is 700-800℃, preferably 720-780℃, and more preferably 740-760℃; the annealing time is 8-20 min, preferably 10-18 min, and more preferably 10-15 min.
[0047] In this invention, the (Na) 0.3 Bi 0.7-x Nd x (Mg) 0.2 Zr 0.2 Ti 0.6-y Mn y The thickness of the O3 ferroelectric thin film is 300-500 nm, preferably 350-450 nm, and more preferably 400 nm.
[0048] The present invention also provides an application of Nd and Mn co-doped sodium bismuth titanate-based ferroelectric thin film in the preparation of capacitors, wherein the structure of the capacitor from bottom to top is: a Si, Pt, Nd, Mn co-doped sodium bismuth titanate-based ferroelectric thin film and Au.
[0049] In this invention, the method for manufacturing the capacitor includes the following steps:
[0050] 1) Prepare (Na) 0.3 Bi 0.7-x Nd x (Mg) 0.2 Zr 0.2 Ti 0.6-y Mn y The O3 ferroelectric thin film was placed on the gold spraying station and covered with a mask.
[0051] 2) Adjust the air pressure inside the gold spray gun and adjust the voltage of the gold spray gun, and maintain this for a period of time;
[0052] 3) Remove the above-mentioned ferroelectric thin film capacitor from the gold spraying machine, place it on the heating table, and keep it warm for a period of time.
[0053] In this invention, the radius of the mask plate is in the range of 0.1 to 0.5 mm, preferably 0.15 to 0.3 mm, and more preferably 0.2 to 0.3 mm.
[0054] In this invention, the air pressure range inside the gold spraying instrument is 0.1 to 0.2 Pa, preferably 0.14 to 0.18 Pa, and more preferably 0.16 Pa.
[0055] In this invention, the voltage range of the gold spraying device is 6-10mA, preferably 7-8mA, and more preferably 7.5mA.
[0056] In this invention, the gold spraying time ranges from 15 to 23 minutes, preferably from 18 to 21 minutes, and more preferably from 20 minutes.
[0057] In this invention, the temperature setting range of the heating table is 250-290°C, preferably 270-290°C, and more preferably 280°C.
[0058] In this invention, the heat preservation time of the ferroelectric thin film capacitor on the heating table is in the range of 17 to 24 minutes, preferably 18 to 21 minutes, and more preferably 20 minutes.
[0059] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0060] Example 1
[0061] (1) Preparation of solution A: Measure 18 mL of acetic acid, according to the molecular formula (Na) 0.3 Bi 0.69 Nd 0.01 (Mg) 0.2 Zr 0.2 Ti 0.59 Mn 0.01 The molar ratio of sodium acetate trihydrate: bismuth nitrate pentahydrate: neodymium nitrate hexahydrate: magnesium acetate tetrahydrate: manganese nitrate tetrahydrate = 30:69:1:20:1 was weighed into O3. 0.4234 g of CH3COONa·3H2O (99% purity), 2.9751 g of Bi(NO3)3·5H2O (99% purity), 0.0351 g of Nd(NO3)3·6H2O (99.9% purity), 0.3466 g of (CH3COO)2Mg·3H2O (99% purity) and 0.0205 g of Mn(NO3)2·4H2O (98% purity) were mixed in acetic acid and stirred in a water bath at 100℃ for 30 min to obtain solution A.
[0062] (2) Preparation of solution B: Measure 18 mL of acetic acid, according to the molecular formula (Na) 0.3 Bi 0.69 Nd 0.01 (Mg)0.2 Zr 0.2 Ti 0.59 Mn 0.01 The molar ratio of manganese nitrate: tetrabutyl titanate: zirconium propoxide in O3 was weighed out as 1:20:59. 0.0197 g of Md(NO3)2·4H2O (purity 98%) was mixed in acetic acid and stirred in a water bath at 100 °C for 30 min. 2.4 mL of acetylacetone was added and stirred at room temperature for 20 min. 1.6394 g of tetrabutyl titanate (purity 98%) was added and stirred at room temperature for 30 min. Then 2.5 mL of deionized water was added and stirred for 10 min. 0.7487 g of zirconium propoxide was added and stirred at room temperature for 10 min. Finally, 4 mL of ethylene glycol was added and stirred at room temperature for 6 h to obtain solution B.
[0063] (3) Mix solution A and solution B, stir at room temperature for 60 min, and then age for 5 days to obtain (Na) 0.3 Bi 0.69 Nd 0.01 (Mg) 0.2 Zr 0.2 Ti 0.59 Mn 0.01 O3 precursor solution;
[0064] (4) Place the clean and dry Si / Pt substrate on the spin coater and press the adsorption button; then apply the (Na) from step (3) to the spin coater. 0.3 Bi 0.69 Nd 0.01 (Mg) 0.2 Zr 0.2 Ti 0.59 Mn 0.01 O3 precursor solution was dropped onto Pt / Si substrate, spin coating speed was set to 3000 r / min, spin coating time was controlled at 30s; the resulting wet film was transferred to a dry adhesive machine and dried at 200℃ for 4min; the dry adhesive film was transferred to a rapid annealing furnace, pyrolyzed at 400℃ for 8min, and then held at 700℃ for 4min.
[0065] (5) Repeat step (4) 10 times, place the film in a tube furnace for annealing, and hold at 700℃ for 10 min to obtain a (Na) film with a thickness of 400 nm. 0.3 Bi 0.69 Nd 0.01 (Mg) 0.2 Zr 0.2 Ti 0.59 Mn 0.01 O3 ferroelectric thin film;
[0066] (6) Prepare (Na) 0.3 Bi 0.69 Nd0.01 (Mg) 0.2 Zr 0.2 Ti 0.59 Mn 0.01 The O3 ferroelectric thin film was placed on the gold spraying table and covered with a mask with a radius of 0.2 mm.
[0067] (7) Adjust the air pressure inside the gold spraying machine to 0.15Pa and adjust the voltage of the gold spraying machine to 8mA, and keep it for 20min.
[0068] (8) Take the above ferroelectric thin film capacitor out of the gold spraying machine, place it on the heating table, set the temperature to 285℃ and keep it for 20 minutes to obtain the capacitor.
[0069] Example 2
[0070] The difference from Example 1 is that the molecular formula is (Na) 0.3 Bi 0.68 Nd 0.02 (Mg) 0.2 Zr 0.2 Ti 0.585 Mn 0.015 O3, the thickness of the ferroelectric thin film is 400nm.
[0071] Example 3
[0072] The difference from Example 1 is that the molecular formula is (Na) 0.3 Bi 0.67 Nd 0.03 (Mg) 0.2 Zr 0.2 Ti 0.58 Mn 0.02 O3, the thickness of the ferroelectric thin film is 400nm.
[0073] Comparative Example 1
[0074] (1) Preparation of solution A: Measure 18 mL of acetic acid, according to the molecular formula (Na) 0.3 Bi 0.7 (Mg) 0.2 Zr 0.2 Ti 0.6 Sodium acetate trihydrate, bismuth nitrate pentahydrate, and magnesium acetate tetrahydrate were weighed out in a molar ratio of 3:7:2. 0.4234 g of CH3COONa·3H2O (99% purity), 3.0182 g of Bi(NO3)3·5H2O (99% purity), and 0.3466 g of (CH3COO)2Mg·3H2O (99% purity) were mixed in acetic acid and stirred in a water bath at 100°C for 30 min to obtain solution A.
[0075] (2) Preparation of solution B: Measure 18 mL of acetic acid, according to the molecular formula (Na) 0.3 Bi 0.7 (Mg) 0.2 Zr 0.2 Ti 0.6 Weigh out tetrabutyl titanate and zirconium propoxide in a molar ratio of 2:6. Pour 2.4 mL of acetylacetone into acetic acid and stir for 20 min. Add 1.6671 g of tetrabutyl titanate (purity 98%) and stir at room temperature for 30 min. Then add 2.5 mL of deionized water and stir for 10 min. Add 0.7487 g of zirconium propoxide and stir at room temperature for 10 min. Finally, add 4 mL of ethylene glycol and stir at room temperature for 6 h to obtain solution B.
[0076] (3) Mix solution A and solution B, stir at room temperature for 60 min, and then age for 5 days to obtain (Na) 0.3 Bi 0.7 (Mg) 0.2 Zr 0.2 Ti 0.6 O3 precursor solution;
[0077] (4) Place the clean and dry Si / Pt substrate on the spin coater and press the adsorption button; then apply the (Na) from step (3) to the spin coater. 0.3 Bi 0.7 (Mg) 0.2 Zr 0.2 Ti 0.6 O3 precursor solution was dropped onto Pt / Si substrate, spin coating speed was set to 3000 r / min, spin coating time was controlled at 30s; the resulting wet film was transferred to dry adhesive machine and dried at 200℃ for 4min; the dry adhesive film was transferred to rapid annealing furnace, pyrolyzed at 400℃ for 8min, and held at 700℃ for 4min.
[0078] (5) Repeat step (4) 10 times, place the film in a tube furnace for annealing, and hold at 700℃ for 10 min to obtain a (Na) film with a thickness of 400 nm. 0.3 Bi 0.7 (Mg) 0.2 Zr 0.2 Ti 0.6 O3 ferroelectric thin film;
[0079] (6) Prepare (Na) 0.3 Bi 0.7 (Mg) 0.2 Zr 0.2 Ti 0.6 The O3 ferroelectric thin film was placed on the gold spraying table and covered with a mask with a radius of 0.2 mm.
[0080] (7) Adjust the air pressure inside the gold spraying machine to 0.15Pa, adjust the voltage of the gold spraying machine to 8mA, and maintain for 20min;
[0081] (8) Take the above ferroelectric thin film capacitor out of the gold spraying machine, place it on the heating table, set the temperature to 285℃ and keep it for 20 minutes to obtain the capacitor.
[0082] As can be seen from the above embodiments, the present invention provides a sodium bismuth titanate-based ferroelectric thin film co-doped with Nd and Mn, its preparation method and application. Figure 1 (Na) prepared in this invention 0.3 Bi 0.7-x Nd x (Mg) 0.2 Zr 0.2 Ti 0.6-y Mn y The schematic diagram of the O3 ferroelectric thin-film microcapacitor shows that it is composed of Si, Pt, a ferroelectric thin film, and Au from bottom to top. Analysis... Figure 2 From the variation trend of the dielectric constant under different proportions, we can draw some important conclusions. In Examples 1-3, the dielectric constant of the material decreased with the increase of Nd and Mn elements introduced at the A-site and B-site. This indicates that Nd has a certain influence on the material properties, and the greater the amount introduced, the more the polarization intensity gradually decreases. According to... Figure 3 The (Na) prepared in Examples 1-3 and Comparative Example 1 are shown. 0.3 Bi 0.7-x Nd x (Mg) 0.2 Zr 0.2 Ti 0.6-y Mn y The leakage current density curves of the O3 ferroelectric thin film material reveal some patterns. With the increase of Nd and Mn elements introduced at the A-site and B-site respectively in the perovskite ABO3 structure, the leakage current density of this ferroelectric thin film material exhibits a trend of first decreasing and then increasing. Notably, in Example 2, this ferroelectric thin film material exhibits a minimum value. This indicates that by appropriately controlling the content of added Nd and Mn elements, the leakage current density can be effectively reduced. Figure 4 Examples 1-3 and Comparative Example 1 (Na) are shown. 0.3 Bi 0.7-x Nd x (Mg) 0.2 Zr 0.2 Ti 0.6-y Mn y Hysteresis loop diagram of O3 miniature capacitor. By observing this diagram, we can see that the hysteresis behavior differs between different embodiments and comparative examples. Figure 5Examples 1-3 and Comparative Example 1 show the (Na) prepared in these examples. 0.3 Bi 0.7-x Nd x (Mg) 0.2 Zr 0.2 Ti 0.6-y Mn y The breakdown strength and polarization intensity of the O3 ferroelectric thin film material are compared. Observation clearly shows that Example 2 exhibits a very high breakdown field strength of 4500 kV / cm and a polarization intensity of 95 μC / cm. 2 This improvement is primarily based on two aspects. First, the increased breakdown field strength is achieved by reducing the leakage current density. Second, the increased polarization intensity is built upon the improved breakdown field strength. Because Example 2 has a higher breakdown field strength, the dipole reversal process is smoother. Under a higher external electric field, the dipoles will instantaneously reverse and rearrange. This reversal behavior leads to a larger and more stable polarization effect, resulting in a significant increase in overall polarization intensity. Through the analysis of… Figure 4 By calculating the hysteresis loop in Examples 1-3 and Comparative Example 1, we obtained the (Na) values. 0.3 Bi 0.7-x Nd x (Mg) 0.2 Zr 0.2 Ti 0.6-y Mn y The energy storage density and energy storage efficiency of O3 microcapacitors. For example... Figure 6 As shown, while maintaining almost the same energy storage efficiency, the energy storage density of these microcapacitors increased by approximately 65%, reaching an astonishing 111.34 J / cm². 3 This result demonstrates that introducing doping elements during the design and fabrication process can significantly improve the performance of microcapacitors. By optimizing the material composition, we have successfully enhanced their ability to store large amounts of charge and release more usable energy. This technological breakthrough opens up broader possibilities for the application of microcapacitors in various fields.
[0083] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A Nd and Mn co-doped sodium bismuth titanate-based ferroelectric thin film, characterized in that: The chemical composition of the Nd and Mn co-doped sodium bismuth titanate-based ferroelectric film is: 0.3 Bi 0.7-x Nd x )(Mg 0.2 Zr 0.2 Ti 0.6-y Mn y )O3, where 0≤x≤0.07, 0≤y≤0.
04.
2. The method for preparing the Nd and Mn co-doped sodium bismuth titanate-based ferroelectric thin film according to claim 1, characterized in that: The following steps are involved: 1) adding sodium acetate, bismuth nitrate, neodymium nitrate and magnesium acetate to acetic acid in sequence according to a stoichiometric ratio to obtain a solution A; 2) adding manganese nitrate, acetylacetone, tetrabutyl titanate, deionized water, zirconium n-propoxide and ethylene glycol to acetic acid in sequence according to a stoichiometric ratio to obtain a solution B; 3) mixing solution A and solution B and aging them to obtain a precursor solution; 4) Spin coating the precursor solution on the substrate, and then drying and heat treating the substrate; 5) Repeat step 4) until the target thickness is reached, and then anneal to obtain (Na 0.3 Bi 0.7-x Nd x )(Mg 0.2 Zr 0.2 Ti 0.6-y Mn y )O3 ferroelectric thin film, wherein 0≤x≤0.07, 0≤y≤0.
04.
3. The method for preparing the Nd and Mn co-doped sodium bismuth titanate-based ferroelectric thin film according to claim 2, characterized in that: The volume ratio of acetylacetone, deionized water and ethylene glycol is 1-3:2-4:3-8; In the step 1), the usage ratio of acetic acid to sodium acetate is 12-20 mL: 0.003 mol; In the step 2), the usage ratio of acetic acid to zirconium n-propoxide is 12-20 mL: 0.002 mol.
4. The method for preparing the Nd and Mn co-doped sodium bismuth titanate-based ferroelectric thin film according to claim 2 or 3, characterized in that: The total concentration of metal cations in the precursor solution is 0.2-0.4 mol / L; and the aging time is 1-7 days.
5. The method for preparing the Nd and Mn co-doped sodium bismuth titanate-based ferroelectric thin film according to claim 4, characterized in that: The spin coating speed is 2500-4500 r / min, the spin coating time is 30-40 s, and the substrate is a Si / Pt sheet.
6. The method for preparing the Nd and Mn co-doped sodium bismuth titanate-based ferroelectric thin film according to claim 2 or 5, characterized in that: The drying temperature is 200-250° C., and the drying time is 3-5 minutes.
7. The method for preparing the Nd and Mn co-doped sodium bismuth titanate-based ferroelectric thin film according to claim 6, characterized in that: The heat treatment is divided into two stages: the first stage is pyrolysis at 400-500°C for 4-12 minutes, and the second stage is heat preservation at 700-800°C for 4-10 minutes.
8. The method for preparing the Nd and Mn co-doped sodium bismuth titanate-based ferroelectric thin film according to claim 2, 5 or 7, characterized in that: The annealing temperature is 700-800° C., and the annealing time is 8-20 minutes.
9. The method for preparing the Nd and Mn co-doped sodium bismuth titanate-based ferroelectric thin film according to claim 8, characterized in that: Said (Na 0.3 Bi 0.7-x Nd x )(Mg 0.2 Zr 0.2 Ti 0.6-y Mn y )The thickness of the O3 ferroelectric film is 300 to 500 nm.
10. The use of the Nd and Mn co-doped sodium bismuth titanate-based ferroelectric film according to claim 1 in the preparation of capacitors, characterized in that: The structures of the capacitor from bottom to top are respectively: Si, Pt, Nd, Mn co-doped sodium bismuth titanate-based ferroelectric film and Au.
Citation Information
Patent Citations
Method for realizing coercive field reduction and pressure resistance improvement of sodium bismuth titanate-based film
CN104496468A
Sodium bismuth titanate based ferroelectric film and preparation method thereof
CN118164754A
Sodium bismuth titanate-based lead-free relaxor ferroelectric energy storage ceramic material with antiferroelectric-like characteristic and preparation method of sodium bismuth titanate-based lead-free relaxor ferroelectric energy storage ceramic material
CN118894722A
Bismuth sodium titanate-barium titanate base piezoelectric ceramic and its prepn process
CN1673178A
Process for the preparation of bismuth sodium titanate
US20220106196A1